Winter Weather Whiplash: Impacts of Meteorological Events Misaligned With Natural and Human Systems in Seasonally Snow‐Covered Regions. Issue 12 (28th December 2019) - Casson, N. J.; Contosta, A. R.; Burakowski, E. A.; Campbell, J. L.; Crandall, M. S.; Creed, I. F.; Eimers, M. C.; Garlick, S.; Lutz, D. A.; Morison, M. Q.; Morzillo, A. T.; Nelson, S. J.
Abstract: "Weather whiplash" is a colloquial phrase for describing an extreme event that includes shifts between two opposing weather conditions. Prior media coverage and research on these types of extremes have largely ignored winter weather events. However, rapid swings in winter weather can result in crossing from frozen to unfrozen conditions, or vice versa; thus, the potential impact of these types of events on coupled human and natural systems may be large. Given rapidly changing winter conditions in seasonally snow‐covered regions, there is a pressing need for a deeper understanding of such events and the extent of their impacts to minimize their risks. Here we introduce the concept of winter weather whiplash, defined as a class of extreme event in which a collision of unexpected conditions produces a forceful, rapid, back‐and‐forth change in winter weather that induces an outsized impact on coupled human and natural systems. Using a series of case studies, we demonstrate that the effects of winter weather whiplash events depend on the natural and human context in which they occur, and discuss how these events may result in the restructuring of social and ecological systems. We use the long‐term hydrometeorological record at the Hubbard Brook Experimental Forest in New Hampshire, USA to demonstrate quantitative methods for delineating winter weather whiplash events and their biophysical impacts. Ultimately, we argue that robust conceptual and quantitative frameworks for understanding winter weather whiplash events will contribute to the ways in which we mitigate and adapt to winter climate change in vulnerable regions. Plain Language Summary: Weather whiplash is a term used by researchers and the media to describe wild and rapid shifts in weather conditions. Here we investigate "winter weather whiplash" events, which are characterized by weather conditions swinging from frozen to unfrozen (or vice versa). These events have important consequences for ecosystems and communities, especially when they occur at unusual times of the year. Impacts of these events include tree damage, flooding, electrical outages, and crop damage. We use a series of case studies to explore the impacts of these events and analyze a long‐term data set to demonstrate how they might be detected from weather data. Understanding winter weather whiplash events will help decision makers and planners adapt and mitigate these events in the future. Key Points: Winter weather whiplash is defined as a rapid change in weather with temperature fluctuations above and below freezing Although rare, these events may have outsized impacts on coupled human and natural systems Identifying the occurrences of these events is critical in light of rapidly changing winter conditions